Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.3 - Fractional Exponents - Problem Set 11.3 - Page 489: 64



Work Step by Step

We will use the rule $a^{n}a^{m}=a^{n+m}$ in the solution. Therefore, $(x^{\frac{2}{5}})(3x^{-\frac{1}{2}})$ $=(1\times3)(x^{\frac{2}{5}-\frac{1}{2}})$ $=(3)(x^{\frac{2(2)-5}{10}})$ $=3x^{\frac{4-5}{10}}$ $=3x^{-\frac{1}{10}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.